Active Fe‐Nx Sites in Carbon Nanosheets as Oxygen Reduction Electrocatalyst for Flexible All‐Solid‐State Zinc–Air Batteries. (21st September 2017) - Wang, Mengfan; Liu, Sisi; Xu, Na; Qian, Tao; Yan, Chenglin
Abstract: Efficient electrocatalysts with accessible active sites are a hot topic due to their potential applications in commercial energy devices. Herein, the synthesis of a superior oxygen electrode catalyst is presented with active Fe‐N x sites in carbon nanosheets, which exhibit prominent catalytic activity toward the oxygen reduction reaction. The high accessibility of Fe‐N x sites is verified by cyanide treatment, and their activity decreases after coordinating with cyanide ions compared with catalysts containing particulate phase active sites. In aqueous zinc–air battery tests, primary batteries with the catalyst as the air electrode demonstrate superior power density and discharge stability. Impressively, flexible all‐solid‐state batteries using gel electrolytes are also assembled and can be used to light a light‐emitting‐diode bracelet, thus holding great potential for practical application in next‐generation electronic devices with portable and wearable characteristics. Abstract : An iron, nitrogen codoped carbon nanosheet is synthesized to be applied in flexible all‐solid‐state zinc–air batteries. A superior oxygen electrode catalyst with highly active Fe‐N x sites delivers prominent catalytic activity toward the oxygen reduction reaction. Flexible all‐solid‐state batteries fabricated with this nanosheet exhibit good flexibility as well as cycling stability and can be used to light an LED bracelet.